2020
DOI: 10.1186/s12906-020-03066-4
|View full text |Cite
|
Sign up to set email alerts
|

Systems pharmacology-based approach to investigate the mechanisms of Danggui-Shaoyao-san prescription for treatment of Alzheimer’s disease

Abstract: Background Alzheimer’s disease (AD) is the most common cause of dementia in the elderly, characterized by a progressive and irreversible loss of memory and cognitive abilities. Currently, the prevention and treatment of AD still remains a huge challenge. As a traditional Chinese medicine (TCM) prescription, Danggui-Shaoyao-san decoction (DSS) has been demonstrated to be effective for alleviating AD symptoms in animal experiments and clinical applications. However, due to the complex components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Scholars have reported that the material basis of DSS against atherosclerosis was paeoniflorin, ferulic acid, and Poria acid, and the material basis of DSS against senile dementia are ferulic acid, A. macrocephala I, gallic acid, etc. ( Wu et al, 2020 ; Bi et al, 2021 ). Nevertheless, for hundreds of years, due to the complexity of the components and internal mechanisms of DSS, tremendous efforts have been made to reveal the active components and pharmacological mechanisms of DSS, but it still has not been effectively solved.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have reported that the material basis of DSS against atherosclerosis was paeoniflorin, ferulic acid, and Poria acid, and the material basis of DSS against senile dementia are ferulic acid, A. macrocephala I, gallic acid, etc. ( Wu et al, 2020 ; Bi et al, 2021 ). Nevertheless, for hundreds of years, due to the complexity of the components and internal mechanisms of DSS, tremendous efforts have been made to reveal the active components and pharmacological mechanisms of DSS, but it still has not been effectively solved.…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology, in combination with the system biology theory, utilizes high-throughput omics data analysis, computer simulation, network database retrieval, and other technologies to construct drug–target–disease interaction networks as well as to systematically clarify the potential targets and pharmacological effects of traditional Chinese medicine (TCM) components to evaluate the role of TCM in diseases ( Nogales et al, 2022 ). Therefore, an increasing number of studies have applied network pharmacology to clarify the pharmacodynamic basis and the molecular mechanism of TCM/drugs in disease treatment ( Luo et al, 2020 ; Wu et al, 2020 ; Cai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 13 Studies have found that the construction of complex biochemical networks of living organisms such as cells presented a large-scale period from transients (such as metabolic reactions) to long-term regulation (such as cell development), from different localities within cells to tissues and organs. 14 Large-scale leaps will also present multiple dimensions of the three-dimensional network from small chemical molecules, genes to proteins. 15 Therefore, systemic pharmacology can solve a series of problems brought about by the complexity of TCM, which provides a new approach to predict the active ingredients and candidate targets through a holistic process of active compound screening, target “fishing”, component–target–disease (C–T–D) network construction, and target enrichment analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic pharmacology is built to study the interaction between drugs and the body from a systemic level, which helps to study the discipline and mechanisms of the action of the drugs, especially some ancient but potent formulae . Studies have found that the construction of complex biochemical networks of living organisms such as cells presented a large-scale period from transients (such as metabolic reactions) to long-term regulation (such as cell development), from different localities within cells to tissues and organs . Large-scale leaps will also present multiple dimensions of the three-dimensional network from small chemical molecules, genes to proteins .…”
Section: Introductionmentioning
confidence: 99%